Use of the new da Vinci Xi® during robotic rectal resection for cancer: a pilot matched‐case comparison with the da Vinci Si®. Issue 1 (25th January 2016) - Morelli, Luca; Guadagni, Simone; Di Franco, Gregorio; Palmeri, Matteo; Caprili, Giovanni; D'Isidoro, Cristiano; Cobuccio, Luigi; Marciano, Emanuele; Di Candio, Giulio; Mosca, Franco
Abstract: Background: The aim of this study was to compare the short‐term outcomes of robotic rectal resection with total mesorectal excision (TME) for rectal cancer, with the use of the new da Vinci Xi® (Xi‐RobTME group) and the da Vinci Si® (Si‐RobTME group). Methods: Ten patients with histologically confirmed rectal cancer underwent robot‐assisted TME with the use of the new da Vinci Xi. The outcomes of Xi‐RobTME group were compared with a Si‐RobTME group selected using a case‐matched methodology. Results: Overall operative times and mean hospital stays were shorter in the Xi‐RobTME group. Surgeries were fully robotic with a complete take‐down of the splenic flexure in all Xi‐RobTME cases, while only four cases of the Si‐RobTME group were fully robotic, with two cases of complete take‐down of the splenic flexure. Conclusions: The new da Vinci Xi could offer some advantages with respect to the da Vinci Si in rectal resection for cancer. Copyright © 2016 John Wiley & Sons, Ltd.